Stories from the Tribunal by Juozapas Tadas Jarockis, an Agent (the Eighteenth Century) - Stankevič, Adam (Senoji Lietuvos literatūra, 2024)
In the post-Lublin Grand Duchy of Lithuania, the Supreme Tribunal of Lithuania, which was the highest court of appeal for the nobility that functioned intermittently from 1582 to 1792, was one of the most important and stable public institutions. The workings of this court were described in the memoirs of its contemporaries and in the periodical press, and daybooks of the Tribunal inauguration or even of its entire term started appearing in the eighteenth century. The court stimulated the cultural life of the towns where it sat and promoted the so-called Tribunal-related creative work (clerical sermons, ceremonial speeches, occasional poems, and the like). At the same time, however, there is a severe lack of sources that would reveal various daily incidents from the activities of this court as well as literary works about its officials and staff. This publication of sources consists of three stories (‘The Son of a Vogt’, ‘Sand for the Scribe’, and ‘The Knight with a Cuirass’), which describe humorous situations in the Supreme Tribunal of Lithuania during the reign of King Augustus III. They were conveyed in a literary form, and the details of the protagonists (court officials, lawyers) and the specific circumstances of the incidents were made as impersonal as possible. The stories were written down by Juozapas Tadas Jarockis, a nobleman of the Breslau district, who in the middle of the eighteenth century worked as an agent (a legal representative in court) at the said court. They found their way into a manuscript book, which Jarockis compiled in the second half of the eighteenth century and referred to as manuskrypt, and which is now kept in the Lithuanian State Historical Archives. The texts in the publication are given in the original language (Polish, with insertions in Latin and Ruthenian) with a translation into Lithuanian.